Can Neighbor Attributes Predict School Absences?. (March 2014) - Gottfried, Michael A.
Recent evidence suggests that the neighborhood context, particularly for urban youth, can influence a range of outcomes. This study makes contributions to the field by examining how the neighborhood context directly relates to missing school. To do so, this study employs a large-scale, longitudinal data set of multilevel observations for entire elementary- and middle-school student cohorts in an urban district over 8 academic years. By linking urban school district administrative data with U.S. Census data, this study provides unique insight into how the characteristics of the neighbors on a student's residential block (determined by his or her exact home address) predict school absences. The results indicate significant relationships between school absences and multiple categories of neighbor attributes, as delineated across measures of poverty, family structure, homeownership status, and race. These results are also distinguishable based on student gender, race and ethnicity, and socioeconomic status.